Michael Clark Review from the Festival's Anniversary Season - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review from the Dance Umbrella Festival's Anniversary Season. PALABRAS CLAVE: Michael Clark, Oh My Goddess.
Dentro del apartado "Silver Jubilee: Dance Umbrella at 25".